MANAJEMEN MUTU PENDIDIKAN DI SMA NEGERI 8 JAKARTA - Moria Augusta Sibuea; Winda Dewi Listyasari; Supadi Supadi (Program Studi Manajemen Pendidikan, 2017)
The study aims to obtain data in SMA Negeri 8 Jakarta which aims to know the quality of education management in SMA Negeri 8 Jakarta. This research was conducted from June 2017 until August 2017. Researcher used qualitative approaches and descriptive methods. Data collection was done through observation, interview, and documentation study. The sources of this research are: Deputy Headmaster of Public Relations Department as well as Responsible of Quality Management System ISO 9001: 2008, Head of School Administration Administration, and Teacher Representative as well as School Quality Internal Audit Team. The quality management planning of education in SMA Negeri 8 Jakarta starts from the preparation of the plan based on the evaluation result of the previous program. Planning is approved at the faculty meeting at the beginning of the school year. The planning process is guided by customer needs, vision, mission, and school goals, as well as government regulations. Implementation of quality management education at SMA Negeri 8 Jakarta involves every element in school according to the capacity and each part. In conducting the implementation of the school guided by the programs that have been agreed, the government regulation, as well as the quality objectives of SMA Negeri 8 Jakarta. Supervision of education quality management at SMA Negeri 8 Jakarta uses several strategies to conduct supervision that is using supervision instrument, customer satisfaction questionnaire learners to program in each school operational area, monitoring activity of OSIS-PK, and so on. Keywords: Total Quality Management (TQM), Planning, Implementation, Supervision.